Prosocial Behavior Among Preschool Children in Coastal and Highland Regions of East Java: A Descriptive Comparative Study - Puspitasari, Ratna Nila; Al Baqi, Safiruddin; Sari, Ima Frafika (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Prosocial behavior in early childhood plays an important role in fostering the ability to sharing, helping, cooperating, and well-being. However, there is limited understanding of how geographical and socio-cultural contexts influence the development of prosocial behavior. This study aims to examine and compare the prosocial development of preschool children living in coastal and highland regions, highlighting how geographical, cultural, and environmental differences may influence early social behavior. The research is driven by the need to better understand contextual factors that shape children's prosocial tendencies or behaviors such as sharing, helping, and cooperating, that are critical for healthy interpersonal relationships and emotional growth. A quantitative comparative approach was employed, using a descriptive method with a Mann–Whitney U statistical test to compare prosocial behavior among preschool children in coastal and highland regions. The findings indicate that children in both regions exhibit a range of prosocial behaviors; however, the frequency and nature of these behaviors differ. Coastal children were more likely to demonstrate spontaneous helping and group-oriented cooperation, possibly due to communal lifestyle practices, while highland children showed more empathy-based behaviors, shaped by strong familial interactions and close-knit community values. The study concludes that environmental context significantly contributes to the development of prosociality in early childhood, with each setting offering unique strengths. These findings underscore the importance of culturally responsive early childhood education that nurtures prosocial behavior in line with local values and social norms. This research contributes to the growing body of literature on sociocultural influences on child development and suggests future studies to explore prosocial behavior through a broader range of ecological and cultural lenses.